Association between vitamin-D deficiency with the presence and severity of diabetic retinopathy in type-2 diabetes mellitus - Sanhita Mukherjee; Kumaresh Chandra Sarkar (Al Ameen Medical College, 2020)
Introduction: Several previous studies shown that vitamin D deficiency is highly prevalent in type 2 diabetes mellitus. Vitamin D has inhibitory effects on inflammation and angiogenesis, which are involved in the development of DR. Objective: To find an association with 25 (OH) Vitamin D levels and Diabetic retinopathy (DR) and also to explore whether any relationship exists between 25 (OH) Vitamin D level and degree of severity of Diabetic Retinopathy. Methods: 58 Type 2 DM patients [32 cases with Diabetic Retinopathy and 26 Control with out Diabetic Retinopathy] were evaluated for their ophthalmic findings, glycaemic status and 25 (OH) Vitamin D levels. They were further sub-divided into Patients with No Retinopathy, Mild to Moderate Retinopathy and Severe Retinopathy. Chi square test, Student t test, ANOVA, Relative Risk and Multivariate logistic regression analysis were performed and a significance level of 0.05 was used. Results: Patients with retinopathy had longer diabetes duration and significantly low 25 (OH) Vitamin D level (p value 0.005364*, 0.002454* respectively) although age of the patients in years showed no significant relationship with retinopathy (p value 0.392599). There is significant inter-group variation in 25 (OH) Vitamin D level among no Retinopathy, mild-moderate Retinopathy and severe Retinopathy group (p value 0.00012*). Patients with 25 (OH) Vitamin D deficiency shows significantly higher risk of developing DR [RR2.70, 95% CI (1.38-4.64), p value: 0.0025] and 25 (OH) Vitamin D level is an independent predictor of DR (p value 0.00027*) but duration of type 2 DM in months is not (p value 0.98). Conclusion: Type 2 DM patients with retinopathy were found to have significant vitamin D deficiency as compared to those without retinopathy.